Sovereignty experiments Korean migrants and the building of borders in northeast Asia, 1860-1945 - Park, Alyssa M. (Cornell University Press, 2019)
"Sovereignty Experiments places Korean migrants and multiple efforts to govern them at the center of a transnational history about the building of modern sovereign states in Northeast Asia at the turn of the twentieth century"--
Keywords: Geschichte 1860-1945; Migration; Grenze; Souveränität; Koreaner; Tumen-Gebiet; Koreans / East Asia / History; Koreans / Russia (Federation) / Russian Far East / History; Korea / Emigration and immigration / History; East Asia / Emigration and immigration / History; Russian Far East (Russia) / Emigration and immigration / History; Borderlands / East Asia / History; Borderlands / Korea / History; Borderlands / Russia (Federation) / Russian Far East / History; Borderlands; Emigration and immigration; Koreans; East Asia; Korea; Russia (Federation) / Russian Far East; History